The face metaphor of a virtual teacher : Development of the engine to convey sad facial expression / Herni Haryati Badrulzaman - Badrulzaman, Herni Haryati (2004)
This research is about developing a face metaphor of a virtual teacher that is used to create a sense of presence in the e-leaming environment, hi this research qualitative information through sad facial expression will be focused on. The expression of the virtual teacher will focus on the mouth area; example of sad facial expression with a closed mouth bent downwards. Exploratory approach is used in the construction of a model for face metaphor of the virtual teacher, hi order to developed the sad facial expression of the virtual teacher, sad engine was first developed. Matlab is used to develop the sad engine. The sad engine was first construct using the technique derived from finite automata before codifying it into Matlab. There was five degree of sadness developed in the sad engine. The virtual teacher was first in the state of expressionless or the neutral state. As more and more incorrect answers were given, the degree of sadness will increased.